THE FOURIER ANALYSIS IN THE TEACHING OF APPLIED MATHEMATICS IN TRANSPORT USING MATLAB - Kulička, Jiří; Berková, Andrea (International Association of Technology, Education and Development (IATED), 2016)
The Fourier’s theorem, which was published during the eighteenth century as a formal solution to the classic wave equation, can be also used for description the physical and technical processes in which occurrences recur in a regular pattern. It provides the mathematical language which enables us to exactly describe the periodical processes. The transport engineers are always looking for techniques to optimize systems with the smallest cost and the highest efficiency which are useful in practice. The aim of this paper is to demonstrate such application of the Fourier series in the transport problem and to show how this issue has been used in the teaching of the applied mathematics and numerical methods in transport at the Jan Perner Transport Faculty, University of Pardubice. Using Matlab, it was revealed that the higher performance of the engine could be obtained without extra work and fuel by the tuning of the length of the intake pipe of a combustion four-stroke single-cylinder gasoline engine. The analysis described in this paper is very valuable for the future automotive engineers.
Fourierova analýza ve výuce aplikované matematiky v dopravě s využitím MATLABU
Keywords: fourier’s theorem, infinite series, transport application, applied mathematics, matlab.; Fourierova věta, nekonečné řady, dopravní aplikace, aplikovaná matematika, MATLAB.